Effects of Zilpaterol and melengestrol acetate on bovine skeletal muscle growth and development - Sissom, Erin Kathryn (Kansas State University, 2009)
Zilpaterol (ZIL) is a β-adrenergic receptor (β-AR) agonist that has been recently approved for use in feedlot cattle to improve production efficiencies and animal performance. One of the mechanisms through which this occurs is increased skeletal muscle growth. Therefore, two experiments were conducted to determine the effects of ZIL both in vivo and in vitro. In the first experiment, ZIL addition to bovine satellite cells resulted in a tendency to increase IGF-I mRNA and increased myosin heavy chain IIA (MHC) mRNA with 0.001 [micro symbol]M and decreased MHC mRNA with 0.01 and 10 [micro symbol]M. There were no effects of ZIL on protein synthesis or degradation. In myoblast cultures, there was a decrease in all three β-AR mRNA, and this was also reported in western blot analysis with a reduction in β2-AR expression due to ZIL treatment. In myotubes, there was an increase in β2-AR protein expression. In the second and third experiment, ZIL improved performance and carcass characteristics of feedlot steers and heifers. Additionally, ZIL decreased MHC IIA mRNA in semimembranosus muscle tissue collected from both steers and heifers. An additional part of the third study was conducted to determine the effects of melengestrol acetate (MGA) on bovine satellite cell and semimembranosus muscle gene expression. There were no effects of MGA on the expression of genes analyzed from semimembranosus muscle tissue collected. However, the addition of MGA to cultured bovine satellite cells resulted in increased β1 and β2-AR mRNA. These experiments aid in our understanding of the mechanism of action of MGA in heifers, as well as the effects of ZIL on both steers and heifers. Furthermore, they increase our knowledge and understanding of the mechanism of action of ZIL, as well as other β-agonists used to promote growth and efficiency in feedlot animals.
Keywords: Beta-adrenergic receptor; Bovine; Satellite cell; Zilpaterol; Melengestrol acetate; Skeletal muscle; Agriculture, Animal Culture and Nutrition (0475)